2020
DOI: 10.1002/adma.201906513
|View full text |Cite
|
Sign up to set email alerts
|

Internal‐Field‐Enhanced Charge Separation in a Single‐Domain Ferroelectric PbTiO3 Photocatalyst

Abstract: Ferroelectric materials with spontaneous polarization‐induced internal electric fields have drawn increasing attention in solar fuel production due to the intrinsic polarized structure. However, the origination of charge separation in these materials at the nano/microlevel is ambiguous owing to the complexity of the multielectric fields. Besides, the observed charge separation ability is far from theoretical expectation. Herein, by spatially resolved surface photovoltage spectroscopy, it is clearly demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
113
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(116 citation statements)
references
References 40 publications
3
113
0
Order By: Relevance
“…[ 51 ] Surprisingly, the saturation polarizations of BiVO 4 /BTO and BiVO 4 :I/BTO supported with PVDF thin films were between those observed for BiVO 4 and BTO supported with PVDF thin films, implying that BiVO 4 /BTO and BiVO 4 :I/BTO heterostructures possessed defined polarization fields, which can act as driving forces to accelerate the separation and transportation of photoexcited charge carriers. [ 29b,52 ] However, the saturation polarizations in the PVDF thin films of BiVO 4 :I/BTO‐Ag and BiVO 4 :I/BTO‐Cu deteriorated rapidly, because the finite Ag and Cu nanoparticles improved on the conductivity. Nevertheless, this phenomenon did not mean that BiVO 4 :I/BTO‐Ag and BiVO 4 :I/BTO‐Cu had poor abilities for separating charge carriers, this occurred because BiVO 4 :I/BTO acted as a carrier for the loaded plasmonic metal nanoparticles and could in addition be used to control the transfer of plasma‐induced charges.…”
Section: Resultsmentioning
confidence: 99%
“…[ 51 ] Surprisingly, the saturation polarizations of BiVO 4 /BTO and BiVO 4 :I/BTO supported with PVDF thin films were between those observed for BiVO 4 and BTO supported with PVDF thin films, implying that BiVO 4 /BTO and BiVO 4 :I/BTO heterostructures possessed defined polarization fields, which can act as driving forces to accelerate the separation and transportation of photoexcited charge carriers. [ 29b,52 ] However, the saturation polarizations in the PVDF thin films of BiVO 4 :I/BTO‐Ag and BiVO 4 :I/BTO‐Cu deteriorated rapidly, because the finite Ag and Cu nanoparticles improved on the conductivity. Nevertheless, this phenomenon did not mean that BiVO 4 :I/BTO‐Ag and BiVO 4 :I/BTO‐Cu had poor abilities for separating charge carriers, this occurred because BiVO 4 :I/BTO acted as a carrier for the loaded plasmonic metal nanoparticles and could in addition be used to control the transfer of plasma‐induced charges.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 e,f and Figure S14 show that the as‐grown b ‐BaTiO 3 nanoparticle exhibits an asymmetric hysteresis behavior in dark, which is attributed to the built‐in field associated with the energy band bending. It is well known that this internal electric field mainly originates from the polarization‐induced depolarization field, driving the photoinduced charge separation [29] . After the 400 nm light irradiation, the photoinduced charges are adsorbed onto the polar surface of b ‐BaTiO 3 and drive away the previously absorbed screening charges, i.e., H + /OH − [30] .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Li et al revealed that the depolarization field a driving force to disperse photogenerated electrons and holes to the opposite polarization facets in single-domain ferroelectric PbTiO 3 nanoplates. Notably, the depolarization field can be directly increased with the increasing particle size along the polarization direction, further improving the photocatalytic hydrogen evolution reaction activity 22 . Despite the promising results obtained with polarized semiconductors, efforts in understanding and further development of this approach are mainly restricted in thin-film photoelectrodes.…”
Section: Introductionmentioning
confidence: 99%